2005
DOI: 10.2737/rmrs-gtr-149
|View full text |Cite
|
Sign up to set email alerts
|

A strategic assessment of forest biomass and fuel reduction treatments in Western States

Abstract: USDA Forest Service. 2005. A strategic assessment of forest biomass and fuel reduction A strategic assessment of forest biomass and fuel reduction A strategic assessment of forest biomass and fuel reduction A strategic assessment of forest biomass and fuel reduction A strategic assessment of forest biomass and fuel reduction treatments in Western States treatments in Western States treatments in Western States treatments in Western States treatments in Western States. Gen. Tech. Rep. RMRS-GTR-149. Fort Collins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Wood products resulting from thinning operations are used in a variety of ways, although currently up to 60% of harvested material remains on-site (Parikka, 2004). An increase in availability of biofuels processing facilities may increase removal and use of thinned material (USDA Forest Service, 2005) which may partially offset harvest cost while meeting some of the increasing demand for biofuels (PageDumroese et al, 2010).…”
Section: Background and Definitionsmentioning
confidence: 98%
“…Wood products resulting from thinning operations are used in a variety of ways, although currently up to 60% of harvested material remains on-site (Parikka, 2004). An increase in availability of biofuels processing facilities may increase removal and use of thinned material (USDA Forest Service, 2005) which may partially offset harvest cost while meeting some of the increasing demand for biofuels (PageDumroese et al, 2010).…”
Section: Background and Definitionsmentioning
confidence: 98%
“…An initial estimate of the potential supply of this fuel treatment wood was developed for five western states (USDA Forest Service, 2005). The study identified a large recoverable residue and merchantable wood resource ranging from a low of 576 million dry tons to a high of 2.1 billion dry tons that could be removed over a period of years.…”
Section: Text Box 32 | Forest Resources Of the United Statesmentioning
confidence: 99%
“…As with other types of silvicultural work, fuel treatments are most costly when they involve difficult conditions such as steep terrain, limited access over low standard forest roads, long transportation distances, expensive labor and fuel, high transaction costs, dense residual stand conditions and costly site preparation and maintenance (Rummer 2008). Mechanical fuel treatments under these conditions can cost thousands of dollars per hectare (Prestemon et al 2008;USDA Forest Service 2005). Less costly treatments are, as would be expected, characterized by more favorable conditions.…”
Section: Fuel Treatment Costsmentioning
confidence: 99%